A Study of Politically Aware Space of Mughal Gardens in India: Exploring the Symmetry and Evolution of Mughal Gardens in India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Garden culture in India goes back to the old days when plants and flowers were grown. Indians set up gardens from the tiny baka to the tiny studyan, but architecture was unrelated to gardening in the Mughal periods. In early Buddhist and Sanskrit literature there is many references to gardens, but they were apparently simply luscious green gardens or sacred groves. The Delhi Sultan's kept and built gardens in India during the medieval period. For keeping Alauddin Khalji's garden, Sultan Firozsha Tughlaq was credited. In the surroundings of Delhi and elsewhere he set up innumerable gardens himself. The Mughal historians showed their disdain for the Sultanate garden because it was not well laid or symmetrical. Abu Fazl remarks in his Ain, Former gardens have been planting without order but more methodical arrangement has been made since Babur's arrival in India. Abul Fasl's account is supposed to be the most prominent and revolutionary feature of Agra's first garden, called Hasht Bihisht, 'Plan with Pfades' (Tarhabandi-i khiyaban), in the Hindusan context. Ahmad Yadgar's statement (Garden of eight Paradise). The plan with walkingways in Hindustan was the first example. Mirza Kamran built another garden in Lahore on the pattern of this garden. Babur himself expressed his dissatisfaction with the 'irregular arrangement of the land and the lack of running water' in his autobiography and directed that the garden be made with running water through the means of rolls, orderly (Siyaq-dar) and symmetrically (tarh-dar) (charkhaha). Thus, Babur started in India with the construction of the four-fold symmetrical gardens in the field of gardening. The overuse of the term charbagh was questioned in recent writings when interpreting the Mughal gardens, since it was found that the Mughal Gardens were not always symmetrical.